Analisis Kompetensi Guru Madrasah Tsanawiyah Dalam Memanfaatkan Tik Pada Proses Pembelajaran Dan Pengembangan Diri - Dandan Irawani (Jurnal Analisa Pemikiran Insan Cendikia (Jurnal APIC), 2021)
This research aims to describe the average value of the competence of the skills of tsanawiyah madrasah teachers in utilizing information and communication technology in the learning and self-development process in the implementation of training in the work area (PDWK) at the office of the ministry of religious affairs mandailing Natal district with a sample of 30 participants. This type of research is descriptive quantitative with survey methods. The data taken is skill value data during the training process. From the results of secondary data processing, for the training eye of making blocks the average value is 87 with a good predicate and the most value of 90 as many as 5 participants; the eyes of the online class creation training using the popular application average score of 88 with a good predicate and the most value of 95 as many as 5 participants; eye training in making attractive percentages using popular applications average value 92 with excellent predicate and the most value of 93 as many as 17 participants; Interactive video content creation training eyes averaged 86 with good predicate and the most value of 80 as many as 15 participants. While the average skill score for all subjects and all participants is 88 with a good predicate and the most value of 86 as many as 6 participants. So the implementation of information technology training of tsanawiyah madrasah teachers in the working area of Mandailing Natal kankemenag conducted by Medan Religious Training Center has been good in improving teacher competence for skills to utilize ICT in the learning and self-development process.